Market Liquidity and Exposure of Hedge Funds - Arjen Siegmann; Denitsa Stefanova (Tinbergen Institute, 2011)
We examine whether the drastic improvement in liquidity in the US stockmarket after 2003 has impacted the systematic exposures of hedge funds to theUS-stock market. The relation between market exposure and Amihud's illiquiditymeasure reverses significantly around a breakpoint situated somewherearound 2003. The results are robust to different fund selection criteria, volatilitytiming, the presence of illiquid holdings and the exact position of the breakpoint. Using the returns to a pairs trading strategy as a sorting criterion forcreating portfolios, we find that the effect is strongest for funds that have a significantlypositive loading on the pairs trading return. The results suggest thatbefore 2003, time-varying illiquidity led to a time-varying long bias in US-stockmarket exposure. The reversal of the relationship points towards liquidity timingby hedge funds in the most recent period, after the introduction of automatedtrading on the New York stock exchange in March 2003.
urn:NBN:nl:ui:31-1871/38532
Keywords: G12; G23; 330; hedge funds; market liquidity; limits to arbitrage; liquidity timing